\(ng^{#}\)-Closed Sets In An Ideal Nano Topological Space - Devi, S.; Rameshpandi, M.; David, S. Antony (Communications in Mathematics and Applications, 2021)
In this paper, we propose to introduce the new classes of \(ng^{#}\)-closed sets, \(n\mathcal{I}_{g^#}\)-closed sets, \(nα g^{#}\)-closed sets and completely nano codense in ideal an nano topological space. Also, we studied the \(n\mathcal{I}_{g^#}\)-closed sets and establish their various characteristic properties.